EFFECTIVENESS OF DEVELOPING THE PHYSICAL PREPARATION OF SKILLED HANDBALL PLAYER GIRLS’ WITH THE HELP OF CIRCULAR TRAINING - Shavkatovich Muminov , Abrorbek (Mental Enlightenment Scientific-Methodological Journal, 2024)
In this article, a training program was used to increase the physical fitness of female handball players, as a result of which the study observed that the physical fitness of female students increased.